Statistical assessment of the wave loads at walls through two-phase CFD modeling of the effects of air compressibility - Formentin, Sara Mizar; Palma, Giuseppina; Alcérreca Huerta, Juan Carlos; Zanuttigh, Barbara (Frontiers in Built Environment, 2023)
The modeling of wave impacts against coastal structures requires the analysis of hundreds or thousands of waves to be statistically meaningful. Long irregular wave attacks, when affordable, can be performed experimentally, but may be inadequate to track the air entrapment and account for air compressibility, which, instead, plays a key role in the wave impacts. On the other hand, long simulations are generally avoided in numerical modeling for computational effort and numerical stability reasons, even more so when two-phase flows and air compressibility are involved. In such a context, this paper presents, for the first time, the application of a plug-in suite developed in the OpenFOAM® environment to the representation of long time series of irregular waves impacting against coastal defenses while solving two compressible fluids. To this purpose, such a plug-in compressible suite was applied to reproduce recent 2D experiments of wave overtopping and wave impacts at smooth dikes with crown walls. The numerical stability of the compressible solver and its adequacy to accurately reproduce the wave reflection and the wave overtopping are first verified by comparing the numerical results with the laboratory tests. Second, the improved representation of the wave pressures and wave forces at the walls obtained with the plug-in compressible suite is shown by comparing its results with the corresponding ones obtained with the incompressible solver. Specifically, the plug-in suite—accounting for the effects of the air compressibility during the impact events—outperforms the incompressible native solver in the capture of the pressure peaks, in the reproduction of the time–pressure trace, and in the statistical analysis of the pressure distribution along the crown wall.